Clinical Features Deserve Consideration for a Urologist in COVID-19. - Nadjafi-Semnani, Mohammad; Simforoosh, Nasser; Ghanbarzadeh, Nahid; Nadjafi-Semnani, Ali (Urology Journal, 2020)
We have studied up-to-date knowledge about the clinical feature of the Novel coronavirus pandemic worth consideration by the urologist. PubMed database, the United States centers for disease control and prevention (CDC), and the World Health Organization (WHO) websites were also accessed. A staging system introduced by Siddiqi et al. for the COVID-19 is acknowledged. Hemodialysis centers are high-risk zones in the outbreak of a COVID-19 epidemic. Symptoms and signs, clinical features, and laboratory findings of the renal transplant patients are almost similar to non-transplanted patients.